Build suspense in the feature film - كامل زيدان, اسيل (lark, 2019)
Summary:The research is that it deals with an important element in the film and drama is the thrill of the filmmakers in order to attract the attention of the recipient and the intensity of the television and film in particular, using it well by the maker of the work is to make the receiver sold to the film and make him prisoner broker like To create a vision and answers and in new ways, thus creating a new reality in which the recipient with all his senses towards the completed because the process of suspense captures the senses and affect the psychological psychology of the recipient or the viewer through the cinematic image of its own flexibility and enormous capabilities to embody the Reality and Imagination Together, in order to delve into the thrill and drama of dramatic work, the research entitled "Building suspense in the novel" and the study here means dealing with the construction of the teaser and how to work through the elements of expression, which leads to the enrichment of visual and intellectual content in the structure of the scene and It achieves its ability to expand and deepen the visual meaning and increase the attractiveness of the recipient to interact with it.The research included a systematic framework for research and included the problem of research by asking the following question: What is (how to build the teaser in the novel?) And the importance it carries and the objectives that seek to achieve with the limits of the limits that move.The theoretical framework for research and previous studies, which have been separated with this research, has included two sections:  The first topic (the elements of suspense term and concept) The second topic (how to build suspense in the film)The researcher recorded a number of indicators, including:Employing the gradient in lighting and color contributes to stirring suspenseThe research procedures, including the research methodology and the research sample, were based on the unit of analysis represented by the shot and the scene. The researcher chose one intentional sample of the mother film. The researcher came out with a number of conclusions as well as conclusions..
Keywords: altashwiq; alsiynama